Dynamics of Single‐Stranded RNA Looping Probed and Photoregulated by Sulfonated Pyrene. Issue 26 (13th July 2020) - Xu, Jie; Tojo, Sachiko; Fujitsuka, Mamoru; Kawai, Kiyohiko
Abstract: RNAs especially the noncoding RNAs which lack protein‐coding capacity but have critical functions in a wide range of cellular processes have received increased attention. They are reported to be associated with normal development and physiology, and their disruption would cause cancer. RNAs are dynamic molecules and the structural transition of them is fundamental to many RNA‐involved cellular processes. The study of transition dynamics is critical to gaining knowledge on how the transition occurs, what factors govern the transition, and how to externally regulate the transition. Previously, we have reported the synthesis of sulfonated pyrene, SPy, and its application as a photoregulator for single‐stranded DNA (ssDNA) looping. Herein, we studied the dynamics of single‐stranded RNA (ssRNA) looping in aqueous solution by using SPy as both a probe and a photoregulator. The rate of end‐to‐end loop formation in ssRNA regulated by SPy upon photostimulation suggests a retarding impact of the ribose 2′‐OH. The results also attest that (rU)n sequences are endowed with higher flexibility compared with (dT)n sequences and demonstrate the slowing down effect of C5‐CH3 group in thymine base on the looping dynamics of polythymine sequences. The photoregulated ssRNA looping observed herein occurs at μs to tens of μs time scales. All the findings provide important insight into the flexibility and structural transition dynamics of oligonucleotides. Abstract : Dynamics of single‐stranded (ssRNA) looping was studied using sulfonated pyrene (SPy) as both a probe and a photoregulator. A retarding effect of ribose 2'‐OH group on ssRNA dynamics was found. Due to the lack of C5‐CH3 group, (rU)n is more flexible than (dT)n and has faster dynamics in solution. Intrinsic flexibility or rigidity is the decisive factor for the structural transition dynamics of short oligonucleotides.